Static characteristics of heterojunction GaAs-AlGaAs diodes for microwave noise - Боцула, О. В. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
Diode where in a cathode the static domain has been formed under certain conditions is considered. An impact ionization, avalanche transit effects and noise generation are arisen іn the such diodes in wide frequency range. The analysis of the diode operation was performed using Monte Carlo technique. The possibility of impact ionization and present of as electron as hole are take into consideration. An insertion of heterojunction influence on maximal electric field position more then its magnitude have been shown. A current – voltage characteristics of considered diodes show the same features. They contain region of sublinear current increasing to be have tendency toward saturation up to certain voltage and superliner growth of current associated with the impact ionization in the domain of a strong field.